Artificial intelligence, financial anxiety and cashier-less checkouts: a Saudi Arabian perspective - Ghazwani, Salman; van Esch, Patrick; Cui, Yuanyuan (Gina); Gala, Prachi (International journal of bank marketing, 2022)
PurposeThis paper aims to investigate the impact of financial anxiety and convenience on the relation between cashier-less versus traditional checkouts and purchase intentions among Saudi Arabian consumers.Design/methodology/approachIn an online experiment, 329 Saudi participants were randomly assigned to one of two checkout conditions (traditional vs. AI-enabled) in a between-subjects design and indicated their financial anxiety. Through moderation-of-process design, the authors examine and showcase that the effect of convenience leads to higher purchase intent for AI-enabled checkouts. Moreover, the authors examine financial anxiety as an underlying mechanism and show that for high-convenience consumers, this enacts higher purchase intent.FindingsThe effect of AI-enabled checkouts depends on consumers' convenience perception. High-convenience consumers prefer AI-enabled checkouts over traditional ones, whereas low-convenience consumers are indifferent. Based on the Roy adaptation model theoretical framework, this occurs because high-convenience consumers experience greater financial anxiety when using AI-enabled checkouts, which in turn leads to higher purchase intent.Originality/valueTo the authors’ knowledge, this is the first study to explore the reactions of Saudi Arabian consumers toward cashier-less stores versus traditional stores. Interestingly, their intent to purchase increases, due to the financial anxiety they experience while encountering AI-enabled transactions. Due to the limited research of retailers going cashier less, little is known about consumer reactions and how they may differ culturally.